2016
DOI: 10.1038/ejhg.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

When knowledge of a heritable gene mutation comes out of the blue: treatment-focused genetic testing in women newly diagnosed with breast cancer

Abstract: for the TFGT Collaborative Group 15Selection of women for treatment-focused genetic testing (TFGT) following a new diagnosis of breast cancer is changing. Increasingly a patient's age and tumour characteristics rather than only their family history are driving access to TFGT, but little is known about the impact of receiving carrier-positive results in individuals with no family history of cancer. This study assesses the role of knowledge of a family history of cancer on psychosocial adjustment to TFGT in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…BM bilateral mastectomy a Self-reported as at 12-months post-enrolment questionnaire and as per medical records for women with missing self-report data b Self-reported as at 12-months post-enrolment questionnaire c Data on intention to undergo BM are missing for 18 women follow-up at the time of completion of cancer treatment. These data support the findings of our qualitative study of women offered TFGT following a new diagnosis of breast cancer [29]. Here it was found that long-term adjustment was hindered by a sense of isolation in women with no family history, and considerable support deficits in these women were observed [29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…BM bilateral mastectomy a Self-reported as at 12-months post-enrolment questionnaire and as per medical records for women with missing self-report data b Self-reported as at 12-months post-enrolment questionnaire c Data on intention to undergo BM are missing for 18 women follow-up at the time of completion of cancer treatment. These data support the findings of our qualitative study of women offered TFGT following a new diagnosis of breast cancer [29]. Here it was found that long-term adjustment was hindered by a sense of isolation in women with no family history, and considerable support deficits in these women were observed [29].…”
Section: Discussionsupporting
confidence: 87%
“…These data support the findings of our qualitative study of women offered TFGT following a new diagnosis of breast cancer [29]. Here it was found that long-term adjustment was hindered by a sense of isolation in women with no family history, and considerable support deficits in these women were observed [29].…”
Section: Discussionsupporting
confidence: 87%
“…Written documents or other resources may be provided in lieu of GC. Fifteen articles, representing nine studies from six countries, were identified ( Table 6 ) [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Although not in the context of a research study, Brierly et al explored a series of cases where pre-test GC was not provided by genetics professionals, and cautioned of the negative outcomes of this model, including unnecessary prophylactic surgeries, unnecessary testing, psychosocial distress, and false reassurance resulting in inappropriate medical management [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining four studies (eight publications) included women diagnosed with ovarian cancer [ 70 , 71 ], breast cancer [ 68 , 69 , 72 , 73 ], or both [ 74 , 75 ]; qualitative and quantitative analyses were published for each patient group. The qualitative data suggested that the impact of GT was minimal in comparison to a cancer diagnosis [ 71 , 72 , 75 ]; however, some women still reported a preference for discussing GT with a health-care provider prior to GT [ 75 ]. The decision to pursue GT was often motivated by altruistic factors [ 71 , 75 ] and to inform treatment [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have assessed patients’ information preferences when offered TFGT; trialing streamlined methods of information dissemination (Quinn et al 2016 ), comparing patients’ views of written information versus face-to-face communication (Meiser et al 2012b ), and examining timing preferences in relation to treatment decision-making (Wevers et al 2017 ). Studies, such as the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) (Plaskocinska et al 2016 ), the DNA-BONus study (Høberg-Vetti et al 2016 ), and others (Augestad et al 2017 ; Meiser et al 2016 ; Wevers et al 2015 /Wevers et al 2016 ) have examined the acceptability and feasibility of TFGT among participants, in order to inform future roll-out of TFGT in clinical practice. Key findings from this research indicate that TFGT is commonly acceptable to patients who appreciate the treatment implications of timely testing (Gleeson et al 2013 ; Meiser et al 2012a /Meiser et al 2012b ; Wevers et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%